HHV-8 infection in patients with AIDS-related Kaposi's sarcoma in Brazil - Keller,R. (2001)
The aims of the present study were to determine the prevalence of human herpesvirus type 8 (HHV-8) in HIV-positive Brazilian patients with (HIV+/KS+) and without Kaposi's sarcoma (HIV+/KS-) using PCR and immunofluorescence assays, to assess its association with KS disease, to evaluate the performance of these tests in detecting HHV-8 infection, and to investigate the association between anti-HHV-8 antibody titers, CD4 counts and staging of KS disease. Blood samples from 66 patients, 39 HIV+/KS+ and 27 HIV+/KS-, were analyzed for HHV-8 viremia in peripheral blood mononuclear cells by PCR and HHV-8 antigenemia for latent and lytic infection by immunofluorescence assay. Positive samples for latent nuclear HHV-8 antigen (LNA) antibodies were titrated out from 1/100 to 1/409,600 dilution. Clinical information was collected from medical records and risk behavior was assessed through an interview. HHV-8 DNA sequences were detected by PCR in 74.3% of KS+ patients and in 3.7% of KS- patients. Serological assays were similar in detecting anti-LNA antibodies and anti-lytic antigens in sera from KS+ patients (79.5%) and KS- patients (18.5%). HHV-8 was associated with KS whatever the method used, i.e., PCR (odds ratio (OR) = 7.4, 95% confidence interval (CI) = 2.16-25.61) or anti-LNA and anti-lytic antibodies (OR = 17.0, 95%CI = 4.91-59.14). Among KS+ patients, HHV-8 titration levels correlated positively with CD4 counts (rho 0.48, P = 0.02), but not with KS staging. HHV-8 is involved in the development of KS in different geographic areas worldwide, as it is in Brazil, where HHV-8 is more frequent among HIV+ patients. KS severity was associated with immunodeficiency, but no correlation was found between HHV-8 antibody titers and KS staging.